Farelo do milho: estrutura, funções nutricionais e aplicação em pães de forma - Corrêa, Renato Ivan (2025)
The growing demand for healthy eating justifies the use of materials rich in dietary fiber. In this sense, the byproduct corn bran, derived from wet-milled corn, is a viable option as a food ingredient due to its functional and beneficial properties. This study aims to characterize the byproduct through centesimal analysis, physical and physicochemical aspects, dietary fiber content, gel formation, and bioactive compounds, as well as its applicability in breads as a substitute for wheat flour. Corn bran, as a raw material, exhibited high luminosity, a yellow color with a tendency to green, a medium particle size suitable for breadmaking, and a high dietary fiber content. Gel formation, with the addition of corn bran, indicated an increase in firmness. Total phenolics and antioxidant activity, as measured by the ABTS+ and FRAP methods, indicate favorable relationships for both bran preservation and its benefits for consumption. Breads with substitutions showed a progressive reduction in specific volume and greater firmness in formulations with higher concentrations. The texture showed greater firmness, and the calculated dietary fiber levels increased, allowing the product to be classified as a high-fiber food. Sensory attributes demonstrated high acceptance rates, indicating the potential of corn bran as an ingredient for enhancing nutritional value and integrating it into bakery products. The results of studies on raw material, bread production, and sensory evaluations suggest that replacing wheat flour with corn bran can benefit consumers.